22.6k views
1 vote
Given the functions k(x) = 2x2 − 7 and p(x) = x − 4, find (k ∘ p)(x).

User Anakha
by
6.4k points

2 Answers

5 votes

Answer:

its c

Explanation:

i took the test

User Mildre
by
6.2k points
1 vote

For this case we have the following functions:


k (x) = 2x ^ 2-7\\p (x) = x-4

We must find
(k_ {0} p) (x). By definition of compound functions we have to:


(k_ {0} p) (x) = k (p (x))

So:

Taking into account that:


(a-b) ^ 2 = a ^ 2-2ab + b ^ 2

Different signs are subtracted and the major sign is placed.


k (p (x)) = 2 (x-4) ^ 2-7 = 2 (x ^ 2-2 (x) (4) + 4 ^ 2) -7 = 2 (x ^ 2-8x + 16) -7 = 2x ^ 2-16x + 32-7 = 2x ^ 2-16x + 25

Finally we have to:


(k_ {o} p) (x) = 2x ^ 2-16x + 25

Answer:


(k_ {o} p) (x) = 2x ^ 2-16x + 25

User Mark Bolusmjak
by
6.3k points